2018
DOI: 10.1111/jvs.12619
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an invasive plant on primary production: Testing a functional trait‐based framework with a greenhouse experiment

Abstract: Questions Predicting when invasive species will affect ecosystem functioning remains problematic, with strong contingency upon both the invasive species and the recipient community's identities. Adopting a functional trait‐based approach might overcome this context‐dependence. As an early exploration of this approach, we used a greenhouse experiment with seeds of the invasive plant Impatiens glandulifera to assess the potential invasion effects on community trait composition and biomass production. Location Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Interestingly, in our study, the initially observed invader impact on litter decomposition, could seemingly be completely explained by changes in the functional trait set of the native community following invasion (invasion status not retained in the final trait models based on CWM values excluding R. rugosa), rather than by the invader's trait set. These results thus add to the literature that illustrates how invader induced ecosystem impacts can be caused by competition effects on the native community's trait composition, rather than directly by the invader's presence (Aerts et al, 2017;Helsen, Kapás, et al, 2018;Helsen, Smith, et al, 2018).…”
Section: Invader Impact On Litter Decompositionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, in our study, the initially observed invader impact on litter decomposition, could seemingly be completely explained by changes in the functional trait set of the native community following invasion (invasion status not retained in the final trait models based on CWM values excluding R. rugosa), rather than by the invader's trait set. These results thus add to the literature that illustrates how invader induced ecosystem impacts can be caused by competition effects on the native community's trait composition, rather than directly by the invader's presence (Aerts et al, 2017;Helsen, Kapás, et al, 2018;Helsen, Smith, et al, 2018).…”
Section: Invader Impact On Litter Decompositionsupporting
confidence: 58%
“…These invader impacts on ecosystem functioning are not necessarily directly driven by the introduction of new functional traits by the invader, but can also be mediated by invader-induced changes in the trait spectrum of the native species in the invaded community (Strayer, 2012). Such trait spectrum changes can be effectuated by invasion-induced changes in species composition (Hejda & de Bello, 2013) or by invasion-induced intraspecific changes in the native species' traits, irrespective of species composition changes (Helsen, Kapás, Rakvaag, Speed, & Graae, 2018;Helsen, Smith, et al, 2018). Even in cases where ecosystem function changes are directly driven by the newly introduced traits of the invader, impacts are usually dependent on the functional distinctiveness of the invader in reference to the trait spectrum of the invaded community (Finerty et al, 2016;Kuebbing & Bradford, 2019;Lee et al, 2017;Pyšek et al, 2012;Scharfy, Funk, Olde Venterink, & Güsewell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This idea is supported by the results of a case study on the invasive herb Impatiens glandulifera , which brought new characteristics into the invaded community, such as tall stature, high SLA, and a low leaf dry matter content (LDMC; Helsen et al. ). On the other hand, Funk et al.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Div ı sek et al (2018) showed that this depends on the invasion stage-naturalized species in central European habitats tend to be similar in their functional traits to native members of the community, while to become invasive, the species need to possess different traits. This idea is supported by the results of a case study on the invasive herb Impatiens glandulifera, which brought new characteristics into the invaded community, such as tall stature, high SLA, and a low leaf dry matter content (LDMC; Helsen et al 2018). On the other hand, Funk et al (2016) demonstrated that invaders in the Mediterranean region tend to be similar to native species in terms of their life-form.…”
Section: Dominant Species' Impacts On Species Richness Species Compomentioning
confidence: 89%
“…Also invader impact on community composition and ecosystem functioning has been hypothesized to depend on the functional distinctiveness of the invader compared to the trait spectrum of the local invaded community (Ehrenfeld 2010, Wardle et al 2011, Drenovsky et al 2012. For several invasive plant species, the invader's distinctiveness in specific traits has been found to be proportional to its impact on ecosystem functions such as biomass production and litter decomposition (Scharfy et al 2011, Finerty et al 2016, Helsen et al 2018a.…”
Section: Inter-and Intraspecific Trait Variation Shape Multidimensional Trait Overlap Between Two Plant Invaders and The Invaded Communitmentioning
confidence: 99%